Divergent differentiation and variant morphology in invasive urothelial carcinomas - association with muscle-invasive disease - Suelen Cunha Santana; Maiara Ferreira de Souza; Maria Estela Pompeu Amaral; Daniel Abensur Athanazio (BMC, 2020)
Abstract Introduction To evaluate the frequency of divergent differentiations / variant morphology in urothelial carcinoma, and their association with muscle-invasive disease at diagnosis. Methods All consecutive cases of invasive urothelial carcinoma from a busy pathology laboratory were reviewed. Clinical and pathological data were recorded including data on divergent and variant morphologies and their percentage within the invasive component. Results Among 91 cases, 46 (51%) showed some form of divergent/variant morphology. The most common divergent morphology was squamous which was present in 18/46 (39% of cases with some divergent or variant morphology) followed by micropapillary (28%), plasmacytoid (20%) and poorly differentiated (17%). Only squamous differentiation was associated with higher rate with muscularis propria invasion. Conclusions Although common, squamous differentiation should be still recognized as a feature of aggressive disease.